2015
DOI: 10.2147/jmdh.s77766
|View full text |Cite
|
Sign up to set email alerts
|

Role of betaine in improving the antidepressant effect of S-adenosyl-methionine in patients with mild-to-moderate depression

Abstract: BackgroundS-adenosyl-methionine (SAMe) is a common add-on treatment used to counteract depressive symptoms in subjects with mild-to-moderate depression, who are low responders to other antidepressant drugs. However, there is some concern about the possible impact of SAMe therapy on homocysteine levels. Betaine is known both to counteract high level of homocysteine in plasma and to increase liquor and plasma levels of SAMe, thus potentiating its effect.AimTo evaluate the role played by betaine, administered alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…It appears that betaine plays a critical role in the regulation of brain functions. A recent clinical study has shown that the combined action of SAMe and betaine is more effective than the administration of SAMe alone in patients with mild to moderate depression (Di Pierro et al 2015). The present animal study revealed that betaine has acute and sustained antidepressant-like effects.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…It appears that betaine plays a critical role in the regulation of brain functions. A recent clinical study has shown that the combined action of SAMe and betaine is more effective than the administration of SAMe alone in patients with mild to moderate depression (Di Pierro et al 2015). The present animal study revealed that betaine has acute and sustained antidepressant-like effects.…”
Section: Discussionsupporting
confidence: 52%
“…A recent clinical study has demonstrated that S-adenosylmethionine (SAMe) plus betaine is more effective than SAMe alone when administered as an add-on therapy to subjects, affected by mild to moderate depression, who were low responders to conventional antidepressants (Di Pierro et al 2015). Although a betaine-alone treatment group was not included in this clinical report and the exact mechanisms underlying the antidepressant effects of betaine remain to be further investigated, apparently betaine has beneficial effects for patients with treatment-resistant depression.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed that SAM increases the efficiency of conventional antidepressants when used together in the treatment of nonresponsive MDD patients [Sarris et al, 2016]. One study demonstrated that the combination of SAM and betaine as an add-on therapy in depressed patients, who did not respond to conventional antidepressants, was more effective than SAM alone [Di Pierro et al, 2015]. Betaine is an alternative methyl group donor in remethylation of methionine (a SAM precursor) from Overall, SAM was comparable to other antidepressants in a therapy of depression.…”
Section: Sam In the Therapy Of Depressionmentioning
confidence: 99%
“…Betaine serves as organic osmolytes and is taken up by cells in situations of environmental stress such as high temp, salinity, osmotic stress, etc. Role of betaine has been well established in treating depression 38 . The lowered concentration of betaine signifies cellular stress in PTSD.…”
Section: Fig 4: Bar Graph Representing Behavioural Activities Performentioning
confidence: 99%